Analysis of Islamic Education Curriculum Development Model Integrating 21st Century Values and Competencies Based - Hazirman, Hazirman; Lona, Devita; Husin, Muhammad; Lahmi, Ahmad; Hakim, Rosniati (Prodi Pendidikan Keagamaan Islam, 2026)
This study aims to examine and formulate a model for developing an Islamic Religious Education curriculum based on the integration of Islamic values and 21st-century competencies. The method used is a literature review by examining various scientific sources in the form of books and national and international journal articles relevant to curriculum studies, Islamic education, and 21st-century competencies. The analysis was conducted descriptively and analytically through data reduction, theme categorization, and concept synthesis to build an integrative and contextual curriculum framework. The results of the study indicate that the development of an effective Islamic Religious Education curriculum model requires a paradigm shift from a content-based curriculum to a value- and competency-based curriculum. The integration of Islamic values, including faith, worship, morals, and muamalah, with 21st-century competencies can be realized through the formulation of holistic learning objectives, the development of contextual materials, the application of active and collaborative learning strategies, and authentic evaluation that assesses cognitive, affective, and psychomotor aspects in a balanced manner. This curriculum model is expected to strengthen the relevance of Islamic Religious Education in shaping students who are religious, have good character, and are ready to face the challenges of global life.